2015
DOI: 10.1007/s13277-015-3182-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in the PRKCG gene and osteosarcoma risk in a Chinese population: a case-control study

Abstract: Osteosarcoma is a common malignant tumor, which exists widely in the bone of children and adolescents. Protein kinase C gamma (PRKCG) gene, which encodes γPKC, plays important roles in tumor promotion, cell proliferation, differentiation, and migration. The objective of the present study was to investigate the relationship between PRKCG polymorphisms and the risk of osteosarcoma. Five tag single nucleotide polymorphisms (SNPs) of PRKCG were retrieved from the HapMap database and genotyped by the method of SNap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Missense variants in exon 4 (C114Y/G123R/ G123E) of the PRKCG gene have a relationship with tumor development and migration (43). Lu et al discovered that PRKCG rs454006 associated with higher OS risk under allele and dominant model (44). Zheng et al predicted that SNP rs454006 could cause a new splice donor site, then lead to incorrect translation of the nuclear cancer proteins, which can regulate oncogene products at the transcription level and result in the development of OS (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missense variants in exon 4 (C114Y/G123R/ G123E) of the PRKCG gene have a relationship with tumor development and migration (43). Lu et al discovered that PRKCG rs454006 associated with higher OS risk under allele and dominant model (44). Zheng et al predicted that SNP rs454006 could cause a new splice donor site, then lead to incorrect translation of the nuclear cancer proteins, which can regulate oncogene products at the transcription level and result in the development of OS (45).…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al. discovered that PRKCG rs454006 associated with higher OS risk under allele and dominant model ( 44 ). Zheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gene mutations in PRKCG promote the occurrence of spinal cord cerebellar ataxia type 14. Additionally, the PRKCG gene plays crucial roles in tumour promotion, cell proliferation, differentiation, and migration by encoding γPKC [23,24]. As shown in Table 2, many changes occurred in the topology of PRKCG.…”
Section: Topological Differential Valuementioning
confidence: 99%
“…Studies have found that mutations in the PRKCG gene increase breast cancer susceptibility [58]. Lu et al [59] also found that PRKCG gene intron variation was significantly associated with an increased risk of osteosarcoma. SAA1 is an acute-phase high-density lipoprotein-associated apolipoprotein that is significantly upregulated in injury, inflammation, and cancer [60].…”
mentioning
confidence: 99%